2021
DOI: 10.1155/2021/2688500
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation, and Hygiene Risk Factors on the Prevalence of Diarrhea among Under-Five Children in the Rural Community of Dangila District, Northwest Ethiopia

Abstract: Background. Under-five diarrhea is one of the major causes of morbidity and mortality in developing countries. Despite the tremendous achievement in reducing child mortality and morbidity in the last two decades, diarrhea is still the major causes of morbidity and mortality in resource-limited countries like Ethiopia due to the absence of clean water and poor sanitation and hygiene. Objective. This study aimed to assess the association of water, sanitation, and hygiene on the prevalence of diarrhea among under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…This study revealed that improved sanitation was associated with a 16% reduction in the risk of diarrhea occurrence among under-five children after matching control and treated children. This finding is in agreement with other studies conducted elsewhere [ 17 , 18 , 21 , 22 , 24 , 27 , 28 , 40 ]. A systematic and meta-analysis conducted by Wolf J et al found that improved sanitation interventions can reduce the occurrence of diarrheal diseases by 24% among children in LMICs [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…This study revealed that improved sanitation was associated with a 16% reduction in the risk of diarrhea occurrence among under-five children after matching control and treated children. This finding is in agreement with other studies conducted elsewhere [ 17 , 18 , 21 , 22 , 24 , 27 , 28 , 40 ]. A systematic and meta-analysis conducted by Wolf J et al found that improved sanitation interventions can reduce the occurrence of diarrheal diseases by 24% among children in LMICs [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, our ndings indicated that children living in households utilizing unsafe sources of drinking water faced a higher likelihood of mortality than those in households with improved water sources. This aligns with previous studies in Ethiopia(Hailu et al, 2021;Mebrahtom et al, 2022). One plausible explanation is the protective role of safe water in preventing water-borne diseases, including diarrheal infections, acute respiratory infections, and neglected tropical diseases, all of which contribute to childhood mortality.…”
supporting
confidence: 90%
“…However, most of the findings used for comparison in this study are results based on short-term studies, which cannot estimate the actual annual prevalence of diarrhea over time ( 25 ). Another possible explanation could be a difference in socioeconomic status, sample size, the accessibility of drinking water, and sanitation facilities ( 26 ). This indicates that more attention should be given to the provision of safe water and access to sanitation facilities in this area.…”
Section: Discussionmentioning
confidence: 99%